The Role of the Ganglion Cell Layer as an OCT Biomarker in Neurodegenerative Diseases - Francesco Ruggeri; Daniele Fumi; Lorena Bassis; Mariachiara Di Pippo; Solmaz Abdolrahimzadeh (Journal of Integrative Neuroscience)
Optical coherence tomography (OCT) is a non-invasive imaging technique in the field of ophthalmology that has been increasingly recognized for its capability to identify potential biomarkers in neurodegenerative processes. While the retinal nerve fiber layer (RNFL) has been vastly explored, this review focuses on the ganglion cell layer (GCL), highlighting its relevance and potential advantages in the diagnostic approach and monitoring of neurodegenerative conditions. In the present review we explore the role of GCL changes detected by OCT in Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). We focus on these conditions due to their prevalence and substantial social impact among neurodegenerative diseases. We summarize key findings on the changes in the GCL and their correlations with disease progression and severity. Moreover, we highlight GCL measurements in the context of a multidisciplinary diagnostic approach, and their potential in adapting tailored therapeutic strategies in neurodegenerative disease management. Challenges such as methodological variability in OCT measurements, automatic instrumental output parameters, the limitations of GCL as a standalone diagnostic tool, and the impact of systemic and ocular factors are discussed. Finally, we propose that forthcoming advancements in OCT technology, integration with other biomarkers, and longitudinal studies will likely further enhance the understanding of GCL changes over time.